(untitled) (Research, Society and Development, 2021)
Senna reticulata (Willd.) H.S.Irwin & Barneby is a plant that is native from the Amazonia rain forest, and popularly known as “matapasto” or “shaman’s leaf”, is a pioneer in open areas, also has food, medicinal, landscape and other uses. For this species, as well as several others from the Amazonia’s biome, there is a lack of information about the biometric aspects of its fruits and its initial development from the seeds, and such information is useful for identification and management. Thus, the present work carried out such a study, through the collection of propagules (fruits and seeds) directly from the canopy of trees located in the city of Belém from Pará, in the Amazonia. One hundred units of fruits and seeds were analyzed in the study of biometric variables: length, width, thickness, standard deviation (σ) and coefficient of variation (CV). The fruits had averages of 12.96 cm length; 1.45 cm wide; 0.22 cm in thickness; and an average of 33 seeds per fruit. The seeds have an average of 6.42 mm length; 2.32 mm wide; and 1.74 mm thick. The water content was 9.9%, while the weight of a thousand seeds is 19 g. As well, 100 units were also analyzed in the germination characterization. The germination begins from the 2nd day of planting, it’s phanerocotyledonar type, and the young plant forms after 33 days, thus reaching the ideal stage for its cultivation.